Alternator Fasa Tiga 12 Volt Untuk Praktik di Laboratorium - Yuwono, Teguh (Universitas Diponegoro, 2006)
Abstract Performing an equipment to train the skille area student of costly adequate 3 phase alternator encumbering enough. so that student fulled the requimen learn skilled of encumbering of 3 phase alternator, need there is solution of levying of unit the skilled alternator 3 phase. One of the way is make by self, modifying car alternator become the 3 phase alternator. Keryord: emf alternator